2013
DOI: 10.1017/s1463423613000170
|View full text |Cite
|
Sign up to set email alerts
|

How do physiotherapists perceive their role in work ability assessments? A prospective focus group study

Abstract: Background: Work ability and work ability assessments have become important both in health care and in relation to granting sick leave. There are different interpretations of work ability among the different professionals involved, and there is no consensus on how work ability should be assessed. Aim: The aim was to analyse how a group of experienced and specially trained physiotherapists (PTs) in primary health care (PHC) perceived their professional role in work ability assessments during 14 months. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It was a new challenge for the physiotherapists to have contact with employers to discuss patients' needs for workplace action. 46 However, the implementation of CDM worked well at the majority of units with minor exceptions. In cluster trials, a potential problem is selection bias if inclusion is systematically different in intervention and control arms.…”
Section: Discussionmentioning
confidence: 99%
“…It was a new challenge for the physiotherapists to have contact with employers to discuss patients' needs for workplace action. 46 However, the implementation of CDM worked well at the majority of units with minor exceptions. In cluster trials, a potential problem is selection bias if inclusion is systematically different in intervention and control arms.…”
Section: Discussionmentioning
confidence: 99%
“…The framework in the International Classification of Functioning, Disability and Health (ICF) is based on a biopsychosocial model. Healthcare professionals' use of the different components in the ICF may contribute to a more informative description of limitations on the patients' ability to work (Stigmar et al, 2013). Some of the participants in our study expressed satisfaction with, or a need for, a more holistic methodology in the healthcare encounters.…”
Section: Mutual Trust In Healthcare Encountersmentioning
confidence: 90%
“…The feeling of being thoroughly assessed and receiving enough time-space seems to strengthen trust. Previous studies have indicated that other healthcare professionals such as physiotherapists or occupational therapists also have knowledge that can supply the assessments that describe the extent and limitations of the person's ability to work (Stigmar et al, 2013;Sturesson et al, 2013).…”
Section: Mutual Trust In Healthcare Encountersmentioning
confidence: 99%
“…The PTs working in primary care in Sweden are often first-line treatment for patients seeking care through open access for musculoskeletal disorders. They often have contact with the patient during a period of time and have therefore adequate knowledge concerning the patient and what is causing the pain which is an advantage in assessing work ability [12,23].…”
Section: Discussionmentioning
confidence: 99%
“…The physiotherapist (PT) often spend a substantial amount of time with the patient and are highly familiar with their functional capacity [10]. Earlier studies indicate that PTs can take responsibility for communication with employers [11,12].…”
Section: Introductionmentioning
confidence: 99%